Proteína degradável no rúmen e frequência de suplementação para novilhos Nelore em pastejo: Desempenho produtivo e análise econômica - De Figueiredo Assad, Leonardo Vaz; Zervoudakis, Joanis Tilemahos; Da Silva Cabral, Luciano; Hatamoto-Zervoudakis, Luciana Keiko; Paulino, Pedro Veiga Rodrigues; De Moraes, Eduardo Henrique Bevitori Kling; Da Silva-Marques, Renata Pereira; Koscheck, Jefferson Fabiano Werner [UNESP] (Universidade Estadual de Londrina, 2015)
It was aimed at to evaluate the effect of the degradable protein in the rumen (RDP) and the supplementation frequency on the average daily gain weight, final body weight and economic viability of cattle in pasture of Brachiaria brizantha cv. Marandu during the rainy/dry transition period. 25 Nellore steers withinitial body weight of 287.96 ±7.47 kg and average initial age of 18 months, distributed into eight paddocks of 1.6 ha each, were used. The experimental design was completely randomized with five replicates and five supplements. The supplements were: SAL - mineral mix supplied ad libitum (Controls); daily RDP: supplement formulated to meet the requirements RDP, with daily supply; frequency RDP: supplement formulated to meet the requirements RDP, supplied three times on week (Mondays, Wednesdays and Fridays); RDP+: supplement formulated with increment of 10% of the requirements of RDP supplied 3X; RDP-: supplement formulated with less 10% of the requirements of RDP supplied 3X. The supplemented animals showed average daily gain (ADG) greater (P = 0. 0010) to control supplement. The RDP daily supplements and RDP frequency showed no significant difference (P> 0. 05) for the GMD. There was a significant difference in ADG of frequency RDP (P = 0. 0189) compared to the RDP-supplement. In the economic evaluation revealed positive economic return to the supplements: frequency RDP, daily RDP, RDP + and RDP-. The strategy of supplying the frequency RDP supplement provided the best economic return. Supplementation in alternate day for grazing steers provides greater gain final and higher body weight ADG, which are effective in promoting economic profitability and higher growth performance to those obtained in the pasture systems daily supply of supplement.
Rumen degradable protein and frequency of supplementation for Nellore steers grazing: Performance and economic analysis
Keywords: Average daily gain; Brachiaria brizantha; Forage; Multiple supplement